PERAN PEOPLE TO PEOPLE DIPLOMACY DALAM HUBUNGAN DIPLOMATIK INDONESIA-MESIR - , RUDI CANDRA, Drs. Dafri Agussalim., MA. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The intimacy between Indonesia and Egypt is the main topic for this research, but this research is more focused on the role of non-government relationship (second track diplomacy). The discussion on this research is based on two main questions: that is, how is the role of the non governmental people in the Egypt-Indonesia diplomatic relation and what factors encourages and discourages those roles. To answer those questions the reasercher will use the theory of constructivism as a prespective to see the phenomena that will backed by the theory of soft power and multy-track diplomacy. This reaserch concludes that the non-government people play an important role in the relationship the two nations. This thesis is compiled as one of the requirements to obtain a post-graduate of international relationship in the Universitas Gadjah Mada.The main purpose of this thesisâ discussion is to give new informations regarding international relationship, especially the relationship between Indonesia and Egypt. Hopefully the reader may view international relationship with more complexity and insights in the future.